Primary Care in Practice Integration is Needed - Capelli, Oreste (IntechOpen, 2016)
The development of the Chronic Care Model (CCM) for the care of patients with chronic diseases has focused on the integration of taking charge of the patient and his family within primary care. The major critical issues in the implementation of the CCM principles are the non-application of the best practices, defined by EBM guidelines, the lack of care coordination and active follow-up of clinical outcomes, and by inadequately trained patients, who are unable to manage their illnesses. This book focuses on these points: the value of an integrated approach to some chronic conditions, the value of the care coordination across the continuum of the illness, the importance of an evidence-based management, and the enormous value of the patients involvement in the struggle against their conditions, without forgetting the essential role of the caregivers and the community when the diseases become profoundly disabling.